2020
DOI: 10.1126/scitranslmed.aay8329
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma β-hydroxybutyrate predicts adverse outcomes and disease progression in patients with arrhythmogenic cardiomyopathy

Abstract: Sudden death could be the first symptom of patients with arrhythmogenic cardiomyopathy (AC), a disease for which clinical indicators predicting adverse progression remain lacking. Recent findings suggest that metabolic dysregulation is present in AC. We performed this study to identify metabolic indicators that predicted major adverse cardiac events (MACEs) in patients with AC and their relatives. Comparing explanted hearts from patients with AC and healthy donors, we identified deregulated metabolic pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 46 publications
1
58
2
Order By: Relevance
“…30 Furthermore, it has recently been shown in the mouse model Myh6-Cre: Dsp w/f that ketogenesis occurs in heart muscle before the development of HF, during early stages of arrhythmogenic cardiomyopathy. 31 The current study revealed a difference in the association of β-OHB with HF between men and women. Besides the well-known differences in the clinical presentation of HF between men and women, with preserved ejection fraction being more frequently observed in women, 32 ketone body metabolism also shows important sex-based differences with a higher production of β-OHB in women.…”
Section: Discussionmentioning
confidence: 55%
“…30 Furthermore, it has recently been shown in the mouse model Myh6-Cre: Dsp w/f that ketogenesis occurs in heart muscle before the development of HF, during early stages of arrhythmogenic cardiomyopathy. 31 The current study revealed a difference in the association of β-OHB with HF between men and women. Besides the well-known differences in the clinical presentation of HF between men and women, with preserved ejection fraction being more frequently observed in women, 32 ketone body metabolism also shows important sex-based differences with a higher production of β-OHB in women.…”
Section: Discussionmentioning
confidence: 55%
“…Ehd1 (Eps15 homology domain-containing protein 1) is recently identified as a novel interactor of Cx43 in the heart and plays a critical role in the pathological remodeling of gap junctions (39). Hmgcs2 is a ketone metabolic enzyme, and the level of Hmgcs2 in patients with arrhythmogenic cardiomyopathy is elevated, which leads to elevated plasma beta-hydroxybutyrate (β-OHB) and predicts major adverse cardiovascular events (MACE) (40). The altered m6A peaks in HFpEF have been associated with several protein processing by GO enrichment and KEGG pathway analyses, such as protein folding, ubiquitin, and protein binding, which means that the dysfunctional m6A methylation of the protein process plays a vital role in the development of HFpEF.…”
Section: Discussionmentioning
confidence: 99%
“…reprogramming described in diverse cancers which involve the overexpression of both HMGC2 (28,29) and PGC-1α transcripts (24). Overexpression of HMGC2/PGC-1α has been observed in high-grade colorectal cancer (30), colitisassociated cancer (31), clear cell renal cell cancer (32,33), ovarian (34), liver (35), oral squamous cell carcinoma (36) and high-grade prostate cancer (37), and is reflective of recurrence and poor prognosis (38).…”
Section: Discussionmentioning
confidence: 99%